Real Exchange Rates, Economic Complexity, and Investment - Brito, Steve (IMF Working Papers; Working Paper, 2018)
We show that the response of firm-level investment to real exchange rate movements varies depending on the production structure of the economy. Firms in advanced economies and in emerging Asia increase investment when the domestic currency weakens, in line with the traditional Mundell-Fleming model. However, in other emerging market and developing economies, as well as some advanced economies with a low degree of structural economic complexity, corporate investment increases when the domestic currency strengthens. This result is consistent with Diaz Alejandro (1963)-in economies where capital goods are mostly imported, a stronger real exchange rate reduces investment costs for domestic firms.